Posouzení vybraného vodního díla za povodní - Šimek, David (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Tato bakalářská práce se zabývá posouzením bezpečnosti vybraného vodního díla Ponětovice při průchodu kontrolní povodňové vlny. Analýza byla provedena v souladu s normou ČSN 75 2935. Práce obsahuje souhrn a popis základních informací o vodním díle, hydraulické výpočty, stanovení mezní bezpečné hladiny, stanovení kontrolní maximální hladiny. Výsledkem práce je zhodnocení současného stavu vodního díla a navržení nápravných opatření.

This bachelor's thesis focuses on the assessment of the safety of the selected hydraulic structure Ponětovice during the passage of a control flood wave. The analysis was carried out in accordance with the ČSN 75 2935. The thesis includes a summary and description of basic information about the hydraulic structure, hydraulic calculations, determination of the limiting safe water level, and the control maximum water level. The outcome of the thesis is an evaluation of the current condition of the hydraulic structure and the proposal of corrective measures.
Evaluation of the Performance of a Specific Water Structure under Flood Conditions
Keywords: Malá vodní nádrž; vodní dílo; manipulační řád; kontrolní povodňová vlna; kontrolní maximální hladina; mezní bezpečná hladina; korunový bezpečnostní přeliv; Small reservoir; hydraulic structure; handling regulations; control flood wave; control maximal water level; maximum permissible water level; crest safety spillway